Propuesta de un manual orgánico funcional para la empresa Princesa Banana #7 del recinto Pimpinela, Cantón Valencia, Provincia de Los Ríos. - Paladines Pereira, Crisstel Ariana (2019)
The functional organic manual is of importance for companies because it allows it to have a structured structure through a management instrument that becomes an aid to clearly define the functions of the different administrative units of the organization, collaborates with the fulfillment of the Strategic Plan and facilitates the coordination of work areas. The objective of this work is to develop an organizational structure and a functional organic manual for the Hcda. Princesa Banana # 7 of the Pimpinela enclosure, Valencia city, province of Los Ríos The 30 permanent workers who work in the company were surveyed, and the administrator was interviewed to obtain information as to the current organization of the company, to finally propose an organizational structure and a functional organic manual in it. The results showed that the lack of an organizational structure in the company has caused problems in defining the true hierarchy with the delimitation of their duties and responsibilities for each of the jobs. The 77% of workers know what functions they should perform in their job and at the same time, they are fully satisfied with their role within the company. Since there is a high degree of ignorance on the part of workers about the usefulness of a functional organizational chart, as well as a functional organic manual (67%), a large majority of the staff indicated that it is important (60%) that these two administrative tools be implemented in the company. The organizational structure proposed in this study establishes three duly structured areas to establish the level of hierarchy in the company in order to reduce the confusion of workers about their immediate bosses. The proposed functional organic manual assigns the activities that people will be in charge of within each job in order to avoid work overload, since this was the main problem manifested by the majority of workers (33%). Key Words: Organization, functions manual, organizational structure.